Metabolic factors and the risk of colorectal cancer by KRAS and BRAF mutation status. Issue 2 (24th January 2019) - Myte, Robin; Gylling, Björn; Häggström, Jenny; Häggström, Christel; Zingmark, Carl; Löfgren Burström, Anna; Palmqvist, Richard; Van Guelpen, Bethany
Abstract : Factors related to energy metabolism and the metabolic syndrome, such as higher body mass index (BMI), blood glucose, or blood lipids, and blood pressure, are associated with an increased risk of colorectal cancer (CRC). However, CRC is a heterogeneous disease, developing through distinct pathways with differences in molecular characteristics and prognosis, and possibly also in risk factors. For subtypes defined by KRAS and BRAF mutation status, BMI is the only metabolic factor previously studied, with inconsistent findings. We investigated whether associations between BMI, blood glucose, blood lipids, and blood pressure and CRC risk differed by tumor KRAS and BRAF mutation status in 117, 687 participants from two population‐based cohorts within the Northern Sweden Health and Disease Study (NSHDS). Hazard ratios (HRs) for overall CRC and CRC subtypes by metabolic factors were estimated with Cox proportional hazards regression, using multiple imputation to handle missing exposure and tumor data. During a median follow‐up of 15.6 years, we acquired 1, 250 prospective CRC cases, of which 766 cases had complete baseline and molecular tumor data. Consistent with previous evidence, higher BMI, total cholesterol, triglyceride levels, and blood pressure were associated with an increased risk of overall CRC (HRs per 1 standard deviation increase: 1.07 to 1.12). These associations were similar regardless of CRC subtype by KRAS and BRAF mutation status (all p heterogeneity > 0.05). The same was true for subtypes based on microsatellite instability status. Poor metabolic health may therefore be a universal mechanism for colorectal cancer, acting across multiple developmental pathways. Abstract : What's new? Factors related to the metabolic syndrome, such as higher body mass index, blood glucose, blood lipids, and blood pressure, are associated with an increased risk of colorectal cancer. However, whether metabolic factors have different roles in different molecular subtypes of colorectal cancer remains an open question. In this population‐based, prospective cohort study of more than 115, 000 people, the answer appears to be no. Metabolic factors were associated with colorectal cancer risk consistently across subtypes based on KRAS and BRAF mutations and microsatellite instability. Poor metabolic health may be a universal mechanism for colorectal cancer, acting across multiple developmental pathways.